Risk of gastrointestinal events among patients with sarcoidosis: a population-based study 1976-2013 - Ungprasert, Patompong; Crowson, Cytnthia S; Matteson, Eric L (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: An increased risk of gastrointestinal (GI) diseases has been observed in immune-mediated disease but the risk in patients with sarcoidosis is not known. Objectives: This study was undertaken to characterize the risk of GI diseases in patients with sarcoidosis. Methods: A population-based cohort of 345 incident cases of sarcoidosis among Olmsted County, Minnesota residents in 1976-2013 was identified. A cohort of 345 sex and age-matched comparators were also identified from the same underlying population. Medical records of both groups were reviewed for GI diseases. Cox models adjusted for age, sex and calendar year were used to compare the rate of development of GI diseases between the groups. In addition, Cox models were used to evaluate the association between use of immunosuppressive agents and the development of GI diseases among patients with sarcoidosis. Results: GI events occurred in 101 cases and 63 comparators, corresponding to an adjusted hazard ratio (HR) of 1.90 (95% confidence interval [CI] 1.38-2.61). Patients with sarcoidosis had an increased risk for both upper (HR 1.90; 95%CI 1.27-2.83) and lower GI events (HR 1.97; 95%CI 1.27-3.05) relative to comparators. By disease type, patients with sarcoidosis had a significantly elevated risk of upper GI ulcer, upper GI hemorrhage and diverticulitis. Regarding medication use, the only significant association was an increased risk of upper GI events among biologic agent users (HR 11.09; 95%CI 2.16-56.97). Conclusion: Patients with sarcoidosis have a higher risk of both upper and lower GI events compared with subjects without sarcoidosis.